The Activin Receptor, Activin-Like Kinase 4, Mediates Toxoplasma Gondii Activation of Hypoxia Inducible Factor-1 - Lis, Agnieszka; Wiley, Mandi; Vaughan, Joan; Gray, Peter C.; Blader, Ira J. (Frontiers in Cellular and Infection Microbiology, 2019)
To grow and cause disease, intracellular pathogens modulate host cell processes. Identifying these processes as well as the mechanisms used by the pathogens to manipulate them is important for the development of more effective therapeutics. As an example, the intracellular parasite Toxoplasma gondii induces a wide variety of changes to its host cell, including altered membrane trafficking, cytoskeletal reorganization, and differential gene expression. Although several parasite molecules and their host targets have been identified that mediate- these changes, few are known to be required for parasite replication. One exception is the host cell transcription factor, hypoxia-inducible factor-1 (HIF-1), which is required for parasite replication in an oxygen-dependent manner. Toxoplasma activates HIF-1 by stabilizing the HIF-1α subunit, and this is dependent on the signaling from the Activin-Like Kinase (ALK) receptor superfamily. Here, we demonstrate that specific overexpression of the ALK family member, ALK4, increased HIF-1 activity in Toxoplasma-infected cells, and this increase required ALK4 kinase activity. Moreover, Toxoplasma stimulated ALK4 to dimerize with its co-receptor, ActRII, and also increased ALK4 kinase activity, thereby demonstrating that Toxoplasma activates the ALK4 receptor. ALK4 activation of HIF-1 was independent of canonical SMAD signaling but rather was dependent on the non-canonical Rho GTPase and JNK MAP kinase signaling pathways. Finally, Toxoplasma increased rates of ALK4 ubiquitination and turnover. These data provide the first evidence indicating that ALK4 signaling is a target for a microbial pathogen to manipulate its host cell.